Strategi Pengembangan Usaha Agroindustri Tempe di Desa Matahoalu Kecamatan Uepai Kabupaten Konawe - Laela Sari; Sarty Syarbiah; Endang Sumiratin (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This study aims to analyze internal and external factors that influence the development strategy of tempeh agroindustry business and formulate a strategy for developing tempeh agroindustry business in Matahoalu Village in Konawe Regency. The method used in this study is the survey method, the case of Pak Iyon's tempeh business in Matahoalu Village. The strengths and weaknesses factor has a total score of 4.27. Because the total score is above 2.5, it means that it identifies a strong internal position. The opportunities and threats factor has a total score of 1.75 because the total score is close to 2.0, it means that it identifies that the business responds to existing opportunities in an extraordinary way and avoids threats to the development of the tempeh agroindustry. The tempeh agroindustry is in the Growth Quadrant where the quadrant is a very profitable situation in that it has opportunities and strengths, so that it can take advantage of existing opportunities, the strategy that must be applied in this condition is to support an aggressive growth policy (Growth Oriented Strategy).